Interactive/automated method to count bacterial colonies - Ribeiro, J.E. (2018)
This study proposes an interactive counting system and a fully automated counting system using image processing methods which are capable to reduce the manpower and time required for counting colonies while taking account colonies both around the central area and boundary areas of a Petri dish.